Photocuring hollow glass bead reinforced bio-based resin composite material and preparation method thereof

By mixing epoxy soybean oil acrylate with isobornyl acrylate and adding hollow glass microbeads, the problems of non-renewable and insufficient physical and mechanical properties of existing photocuring resin raw materials are solved, and higher strength and modulus are achieved, improving The overall performance of the material.

CN119463016APending Publication Date: 2025-02-18VIGIT NEW MATERIAL TECHNOLOGY (TAIZHOU) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411641894.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing photocuring resins have problems such as non-renewable raw materials, release of volatile organic matter, insufficient rigidity and poor physical and mechanical properties.

Method used

The bio-based resin is prepared by mixing epoxy soybean oil acrylate and isoborne acrylate, and hollow glass microbeads are added as reinforcement material during the photocuring process.

Benefits of technology

The tensile strength, tensile modulus, bending strength and bending modulus of bio-based resin are improved, the processing and construction performance of the material are improved, and the release of volatile organic matter is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463016A_ABST
    Figure CN119463016A_ABST
Patent Text Reader

Abstract

According to the light-cured hollow glass bead reinforced bio-based resin composite material and the preparation method, the epoxidized soybean oil acrylate, the isobornyl acrylate and the photoinitiator are mixed, meanwhile, the hollow glass beads are added to serve as a reinforcing body, and the hollow glass bead reinforced bio-based resin composite material is prepared under the irradiation of ultraviolet rays. The bio-based composite material prepared by the invention is environment-friendly and light in weight, and has very high tensile strength, tensile modulus, bending strength and bending modulus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomass composite materials, in particular to a light-cured hollow glass microsphere reinforced bio-based resin composite material and a preparation method thereof. Background Art

[0002] Photocurable resin is a polymer material that can be quickly cured under specific light sources. It has the characteristics of fast curing speed, high production efficiency, and can be coated on various substrates. It is widely used in coatings, adhesives, 3D printing inks and other fields. However, existing photocurable resins have the following disadvantages: 1. Traditional photocurable resins are mainly acrylate systems. The raw materials of commercial photocurable resins are mostly non-renewable fossil resources, and there is a problem of volatile organic compound release.

[0003] 2. The general epoxy soybean oil acrylate molecular structure contains three long flexible molecular chains, with a large molecular weight and high viscosity. The resin after curing is not rigid enough, and its physical and mechanical properties are difficult to meet the requirements of use.

[0004] 3. The strength of pure resin materials is often limited, and there are problems such as low strength, insufficient rigidity, and poor impact resistance. In addition, pure resin materials have a high density and poor thermal performance. Summary of the invention

[0005] The present invention aims to solve the problems existing in the above-mentioned prior art, and therefore proposes a light-cured hollow glass microsphere reinforced bio-based resin composite material and a preparation method thereof.

[0006] In order to achieve the above-mentioned invention object, the following technical scheme is adopted: A light-cured hollow glass microsphere reinforced bio-based resin composite material and a preparation method thereof, including the preparation of a bio-based resin and the preparation of a hollow glass microsphere reinforced bio-based resin composite material, wherein the preparation steps of the bio-based resin include: S1: A certain amount of epoxidized soybean oil acrylate AESO and isobornyl acrylate IBOA were mixed in a three-necked flask, and then a photoinitiator was added, and the mixture was continuously stirred at room temperature to obtain a uniformly mixed bio-based resin; S2: Pour the evenly mixed bio-based resin into the mold, let it stand at room temperature to defoam, then irradiate it under ultraviolet light, and take out the bio-based resin after irradiation molding.

[0007] The preparation steps of the hollow glass microsphere reinforced bio-based resin composite material include: K1: A certain amount of epoxidized soybean oil acrylate AESO and isobornyl acrylate IBOA were mixed in a three-necked flask, and then a photoinitiator was added and stirred continuously at room temperature to obtain a uniformly mixed bio-based resin; K2: Place the hollow glass microspheres HGM into the bio-based resin, place it in an ultrasonic water bath, and mechanically stir it in water; K3: After mixing evenly, pour it into the mold, let it stand at room temperature to defoam, then irradiate it under ultraviolet light. After irradiation and molding, take out the composite material.

[0008] Preferably, the raw material composition includes, by mass: 10-90 parts of epoxy soybean oil acrylate, 10-90 parts of isobornyl acrylate, 2-3 parts of photoinitiator and 1-3 parts of hollow glass microspheres.

[0009] Preferably, the epoxy soybean oil acrylate is a vegetable oil derivative after acrylate esterification, and has a viscosity of 8000~20000 mPa·s at 22~24°C. The isobornyl acrylate is a pinenyl acrylate functional monomer, and has a viscosity of 6~10 mPa‧s at 25~27°C. It contains a rigid cyclic structure. After the epoxy soybean oil acrylate is mixed with isobornyl acrylate, the viscosity of the bio-based resin is reduced, the strength and modulus are increased, thereby improving the processing performance and construction performance.

[0010] Preferably, the photoinitiator is diphenylphosphine oxide (TPO), and the amount of the photoinitiator used is 1-5% of the total mass of the resin.

[0011] Preferably, the hollow glass microspheres are hollow spherical powders whose main component is borosilicate, with a particle size of 10-250 μm and a wall thickness of 1-2 μm. The hollow glass microspheres have high strength and heat resistance, and can further improve the strength and modulus of the bio-based resin.

[0012] Preferably, in the step S1 and the step K1, stirring is continued at room temperature, the room temperature is 20-30° C., the stirring time is 25-35 min, and the mass ratio of the epoxy soybean oil acrylate to the isobornyl acrylate is 9:1 to 1:9.

[0013] Preferably, in step K2, the ultrasonic power of the ultrasonic water bath is 20-200 W, the water bath temperature is 30-90° C., and the stirring time is 25-35 min. Stirring under such conditions can better mix the bio-based resin and the hollow glass microspheres.

[0014] Preferably, in step S2 and step K3, the mold is a polytetrafluoroethylene mold, and the shape of the mold includes a dumbbell-shaped mold and a long strip mold, which is convenient for subsequent performance and modulus testing.

[0015] Preferably, after the bubbles in the bio-based resin disappear in step S2 and step K3, the resin is irradiated under ultraviolet light, the wavelength of the ultraviolet light is 400-430 nm, and the irradiation time is 3-6 minutes. Ultraviolet light irradiation can promote photocuring of the resin.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts epoxidized soybean oil acrylate as a bio-based raw material, which is a commercialized vegetable oil derivative derived from renewable soybean oil resources, thereby solving the problem that the raw materials of traditional photocurable resins are mostly non-renewable fossil resources, and the photocuring process is relatively mild, reducing the volatile substances that may be generated during the high-temperature curing process; the present invention mixes acrylate isobornyl ester with epoxidized soybean oil acrylate to prepare a bio-based resin, and acrylate isobornyl ester has the characteristics of a rigid cyclic structure and a small molecular weight, which can improve the tensile strength, tensile modulus, flexural strength and flexural modulus of the bio-based resin; the present invention adds hollow glass microspheres as a reinforcing material, and the hollow glass microspheres have the properties of light weight, high strength, good fluidity, good heat resistance and the like. Compared with the composite material without adding hollow glass microspheres, the composite material prepared after adding hollow glass microspheres has significantly higher tensile strength, tensile modulus, flexural strength and flexural modulus. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of tensile properties and tensile modulus of bio-based resin in an embodiment of the present invention; Figure 2 Schematic diagram of the bending properties and bending modulus of the bio-based resin in an embodiment of the present invention; Figure 3 Schematic diagram of tensile strength and tensile modulus of hollow glass microsphere reinforced bio-based resin composite material in an embodiment of the present invention; Figure 4 Schematic diagram of the flexural strength and flexural modulus of the hollow glass microsphere reinforced bio-based resin composite material in an embodiment of the present invention; Figure 5 Schematic diagram of the dynamic thermomechanical analysis DMA curve of the bio-based resin and glass microsphere reinforced composite material in the embodiment of the present invention; DETAILED DESCRIPTION

[0018] Hereinafter, the light-cured hollow glass microsphere reinforced bio-based resin composite material and the preparation method of the present invention are specifically described in conjunction with embodiments.

[0019] The invention comprises the preparation of bio-based resin and the preparation of hollow glass microsphere reinforced bio-based resin composite material, wherein the preparation steps of the bio-based resin include: S1: A certain amount of epoxidized soybean oil acrylate AESO and isobornyl acrylate IBOA were mixed in a three-necked flask, and then a photoinitiator was added, and the mixture was continuously stirred at room temperature to obtain a uniformly mixed bio-based resin; S2: Pour the evenly mixed bio-based resin into the mold, let it stand at room temperature to defoam, then irradiate it under ultraviolet light, and take out the bio-based resin after irradiation molding.

[0020] The preparation steps of the hollow glass microsphere reinforced bio-based resin composite material include: K1: A certain amount of epoxidized soybean oil acrylate AESO and isobornyl acrylate IBOA were mixed in a three-necked flask, and then a photoinitiator was added and stirred continuously at room temperature to obtain a uniformly mixed bio-based resin; K2: Place the hollow glass microspheres HGM into the bio-based resin, place it in an ultrasonic water bath, and mechanically stir it in water; K3: After mixing evenly, pour it into the mold, let it stand at room temperature to defoam, then irradiate it under ultraviolet light. After irradiation and molding, take out the composite material. Example

[0021] Preparation process of bio-based resin: 27 g AESO, 3 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, mixed evenly and poured into a polytetrafluoroethylene mold, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0022] In the preparation process, the mass ratio of AESO to IBOA is 9:1; the amount of initiator used is 2% of the mass of the mixture. Example

[0023] Preparation process of bio-based resin: 24 g AESO, 6 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, mixed evenly and poured into a polytetrafluoroethylene mold, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0024] In the preparation process, the mass ratio of AESO to IBOA is 8:2; the amount of initiator used is 2% of the mass of the mixture. Example

[0025] Preparation process of bio-based resin: 21 g AESO, 9 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, mixed evenly and poured into a polytetrafluoroethylene mold, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0026] In the preparation process, the mass ratio of AESO to IBOA is 7:3; the amount of initiator used is 2% of the mass of the mixture. Example

[0027] Preparation process of bio-based resin: 18 g AESO, 12 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, poured into a polytetrafluoroethylene mold after mixing evenly, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0028] In the preparation process, the mass ratio of AESO to IBOA is 6:4; the amount of initiator used is 2% of the mass of the mixture. Example

[0029] Preparation process of bio-based resin: 15 g AESO, 15 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, mixed evenly and poured into a polytetrafluoroethylene mold, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0030] In the preparation process, the mass ratio of AESO to IBOA is 5:5; the amount of initiator used is 2% of the mass of the mixture. Example

[0031] Preparation process of bio-based resin: 12 g AESO, 18 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, mixed evenly and poured into a polytetrafluoroethylene mold, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0032] In the preparation process, the mass ratio of AESO to IBOA is 4:6; the amount of initiator used is 2% of the mass of the mixture. Example

[0033] Preparation process of bio-based resin: 9 g AESO, 21 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, poured into a polytetrafluoroethylene mold after mixing evenly, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0034] In the preparation process, the mass ratio of AESO to IBOA is 3:7; the amount of initiator used is 2% of the mass of the mixture. Example

[0035] Preparation process of bio-based resin: 6 g AESO, 24 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, poured into a polytetrafluoroethylene mold after mixing evenly, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0036] In the preparation process, the mass ratio of AESO to IBOA is 2:8; the amount of initiator used is 2% of the mass of the mixture. Example

[0037] Preparation process of bio-based resin: 3 g AESO, 27 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask, mechanically stirred at 25 °C for 30 min, poured into a polytetrafluoroethylene mold after mixing evenly, and taken out after irradiation with ultraviolet light at a wavelength of 405 nm for 5 min.

[0038] In the preparation process, the mass ratio of AESO to IBOA is 1:9; the amount of initiator used is 2% of the mass of the mixture.

[0039] like Figure 1 and Figure 2 As shown, by analyzing and comparing the tensile strength, tensile modulus, flexural strength and flexural modulus of Examples 1 to 9, it is finally determined that Example 7 is the optimal group. Therefore, Example 7 is selected to prepare a composite material, and its performance is further analyzed. Example

[0040] Preparation process of bio-based resin: 9 g AESO, 21 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask and mechanically stirred at 25 °C for 30 min to obtain the bio-based resin.

[0041] Preparation method of hollow glass microsphere reinforced bio-based resin composite material: 0.3 g hollow glass microspheres are placed in a bio-based resin, placed in an ultrasonic water bath with a power of 80 W, mechanically stirred at 500 r / min at 80 ° C for 30 min to mix evenly, then poured into a mold, placed under ultraviolet light with a wavelength of 405 nm for 5 min to form, and taken out after forming.

[0042] In the preparation process, the mass ratio of AESO to IBOA is 3:7; the amount of the initiator is 2% of the mass of the mixture, and the mass of the hollow glass microspheres is 1% of the mass of the mixture. Example

[0043] Preparation process of bio-based resin: 9 g AESO, 21 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask and mechanically stirred at 25 °C for 30 min to obtain the bio-based resin.

[0044] Preparation method of hollow glass microsphere reinforced bio-based resin composite material: 0.6 g hollow glass microspheres are placed in a bio-based resin, placed in an ultrasonic water bath with a power of 80 W, mechanically stirred at 500 r / min at 80 ° C for 30 min to mix evenly, then poured into a mold, placed under ultraviolet light with a wavelength of 405 nm for 5 min to form, and taken out after forming.

[0045] In the preparation process, the mass ratio of AESO to IBOA is 3:7; the amount of the initiator is 2% of the mass of the mixture, and the mass of the hollow glass microspheres is 2% of the mass of the mixture. Example

[0046] Preparation process of bio-based resin: 9 g AESO, 21 g IBOA and 0.6 g photoinitiator were placed in a 250 mL flask and mechanically stirred at 25 °C for 30 min to obtain the bio-based resin.

[0047] Preparation method of hollow glass microsphere reinforced bio-based resin composite material: 0.9 g hollow glass microspheres are placed in a bio-based resin, placed in an ultrasonic water bath with a power of 80 W, mechanically stirred at 500 r / min at 80 ° C for 30 min to mix evenly, then poured into a mold, placed under ultraviolet light with a wavelength of 405 nm for 5 min to form, and taken out after forming.

[0048] In the preparation process, the mass ratio of AESO to IBOA is 3:7; the amount of the initiator is 2% of the mass of the mixture, and the mass of the hollow glass microspheres is 3% of the mass of the mixture.

[0049] The bio-based resin and composite material obtained in Examples 1 to 12 were subjected to mechanical property tests: Dumbbell-shaped specimens (100 mm long, 10 mm wide at both ends, 5 mm wide in the middle, 25 mm span, and 2.0 mm thickness) of bio-based resins and composite materials were used to test tensile properties; the bending properties were tested in the form of long strips (100 mm long and 10 mm wide). The tensile properties test was carried out in accordance with GB / T 1040.1-2018; the bending properties test was carried out in accordance with GB / T 9341-2008. The tensile and bending properties tests were completed on a microcomputer-controlled electronic universal testing machine.

[0050] Dynamic mechanical properties analysis: The dynamic mechanical properties analysis of bio-based resins and composites was performed on a Q800 DMA instrument. The tests were performed on rectangular samples (length: 55 mm, width: 10 mm) in three-point bending mode, with a temperature range of ‒50~150 °C, a heating rate and a frequency of 3 °C / min and 1 Hz, respectively.

[0051] In Examples 1 to 12, the sample numbers and the corresponding raw material ratios are as follows: A9I1 indicates a bio-based resin with a mass ratio of AESO to IBOA of 9:1; A8I2 represents a bio-based resin with a mass ratio of AESO to IBOA of 8:2; A7I3 indicates a bio-based resin with a mass ratio of AESO to IBOA of 7:3; A6I4 indicates a bio-based resin with a mass ratio of AESO to IBOA of 6:4; A5I5 indicates a bio-based resin with a mass ratio of AESO to IBOA of 5:5; A4I6 represents a bio-based resin with a mass ratio of AESO to IBOA of 4:6; A3I7 indicates a bio-based resin with a mass ratio of AESO to IBOA of 3:7; A2I8 represents a bio-based resin with a mass ratio of AESO to IBOA of 2:8; A1I9 represents a bio-based resin with a mass ratio of AESO to IBOA of 1:9; A3I7-1% refers to a composite material with A3I7 as the matrix and 1% glass beads as reinforcement; A3I7-2% refers to a composite material with A3I7 as the matrix and 2% glass beads as reinforcement; A3I7-3% refers to a composite material with A3I7 as the matrix and 3% glass beads as the reinforcement.

[0052] Depend on Figure 1 It can be seen that the tensile strength and tensile modulus of bio-based resins change with the change of IBOA content, first showing an increasing trend from A9I1 to A2I8, and then showing a decreasing trend from A2I8 to A1I9. When the mass fraction of AESO and IBOA is 2:8, the tensile strength reaches a maximum value of 234 MPa, and the tensile modulus reaches 777 MPa.

[0053] Depend on Figure 2It can be seen that the flexural strength and flexural modulus of bio-based resins change with the change of IBOA content, first showing an increasing trend from A9I1 to A3I7, and then showing a decreasing trend from A3I7 to A1I9. When the mass fraction of AESO and IBOA is 3:7, the flexural strength reaches a maximum value of 334 MPa, and the flexural modulus reaches 513 MPa.

[0054] Depend on Figure 3 It can be seen that after adding hollow glass microspheres, the tensile strength and tensile modulus of the composite material change with the change of glass microsphere content, first showing an increasing trend from A3I7 to A3I7-2%, and then showing a decreasing trend from A3I7-2% to A3I7-3%; when 2% hollow glass microspheres are added, the tensile strength and tensile modulus of the composite material are the best, which are 30 MPa and 1087 MPa, respectively, which are 30% and 80% higher than those of pure resin, respectively.

[0055] Depend on Figure 4 It can be seen that in terms of flexural modulus, the flexural modulus of the composite material is significantly improved after adding hollow glass microspheres. When the mass fraction of glass microspheres is 1%, the flexural modulus of the composite material increases to 1317 MPa, which is 157% higher than that of pure resin. In terms of flexural strength, after adding hollow glass microspheres, the flexural strength of the composite material gradually decreases.

[0056] Depend on Figure 5 It can be seen that with the increase of IBOA dosage, the storage modulus of the resin increases significantly in the glassy stage; at the same time, the addition of glass microspheres also significantly increases the storage modulus of the resin. When the IBOA dosage increases from 60% to 80%, the glass transition temperature of the resin increases from 49.9 ℃ to 62.2 ℃, but the addition of glass microspheres does not significantly affect the glass transition temperature of the composite material. The glass transition temperatures of A3I7 and A3I7-2% are 52.6℃ and 53.6℃, ​​respectively.

[0057] The above description is only a preferred example of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have other optimization schemes and additional functions. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A light-cured hollow glass microsphere reinforced bio-based resin composite material and a preparation method thereof, characterized in that: The preparation steps of the bio-based resin include: S1: A certain amount of epoxidized soybean oil acrylate AESO and isobornyl acrylate IBOA were mixed in a three-necked flask, and then a photoinitiator was added, and the mixture was continuously stirred at room temperature to obtain a uniformly mixed bio-based resin; S2: Pour the evenly mixed bio-based resin into the mold, let it stand at room temperature to defoam, then irradiate it under ultraviolet light, and take out the bio-based resin after irradiation molding.

2. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method according to claim 1, characterized in that: The preparation steps of the hollow glass microsphere reinforced bio-based resin composite material include: K1: A certain amount of epoxidized soybean oil acrylate AESO and isobornyl acrylate IBOA were mixed in a three-necked flask, and then a photoinitiator was added and stirred continuously at room temperature to obtain a uniformly mixed bio-based resin; K2: Place the hollow glass microspheres HGM into the bio-based resin, place it in an ultrasonic water bath, and mechanically stir it in water; K3: After mixing evenly, pour it into the mold, let it stand at room temperature to defoam, then irradiate it under ultraviolet light. After irradiation and molding, take out the composite material.

3. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 1, characterized in that: The raw material composition includes, by weight: 10-90 parts of epoxy soybean oil acrylate, 10-90 parts of isobornyl acrylate, 2-3 parts of photoinitiator and 1-3 parts of hollow glass microspheres.

4. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 1, characterized in that: The epoxy soybean oil acrylate is a vegetable oil derivative after acrylate esterification, and has a viscosity of 8000-20000 mPa·s at 22-24°C. The isobornyl acrylate is a pinenyl acrylate functional monomer, and has a viscosity of 6-10 mPa‧s at 25-27°C, and contains a rigid ring structure.

5. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 1, characterized in that: The photoinitiator is diphenylphosphine oxide (TPO), and the amount of the photoinitiator is 1-5% of the total mass of the resin.

6. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 2, characterized in that: The hollow glass microspheres are hollow spherical powders, the main component of which is borosilicate, with a particle size of 10-250 μm and a wall thickness of 1-2 μm.

7. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 1 or 2, characterized in that: In the step S1 and the step K1, stirring is continued at room temperature, the room temperature is 20-30° C., the stirring time is 25-35 min, and the mass ratio of the epoxy soybean oil acrylate to the isobornyl acrylate is 9:1 to 1:

9.

8. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 2, characterized in that: In step K2, the ultrasonic power of the ultrasonic water bath is 20-200 W, the water bath temperature is 30-90° C., and the stirring time is 25-35 min.

9. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 1 or 2, characterized in that: In the step S2 and the step K3, the shape of the mold includes a dumbbell-shaped mold and a long strip-shaped mold.

10. The light-cured hollow glass microsphere reinforced bio-based resin composite material and preparation method as claimed in claim 1 or 2, characterized in that: After the bubbles in the bio-based resin disappear in step S2 and step K3, the resin is irradiated under ultraviolet light, the wavelength of the ultraviolet light is 400-430nm, and the irradiation time is 3-6 minutes.

Citation Information

Patent Citations

  • Anti-ultraviolet PVC color masterbatch

    CN106380720A

  • Epoxy grease-based unsaturated ester light-cured resin as well as preparation method and application thereof

    CN107383270A

  • Vegetable-oil-based ultraviolet-photocured 3D printing resin friendly to environment and human bodies

    CN108587100A

  • Anti-warping environment-friendly functional master batch with synergistic flame retardance and preparation method thereof

    CN110527195A

  • Reactive hollow microspheres with controllable mechanical properties and preparation method thereof

    CN113771259A